Estrategia interactiva digital para el desarrollo en herramientas tecnológicas en la I.E.P. Alas Peruanas de la Victoria - Chiclayo - Temoche Rojas, Carlos Eduardo (2023)
The objective of this work is to apply a digital interactive strategy, which takes into account the technological didactics for the development of technological tools in the I.E.P. Alas Peruanas de La Victoria - Chiclayo. The causes that originate the problem are examined: practical and theoretical limitations in the digital interactive process, deficient didactic orientation in the digital interactive process by teachers, which allows them to develop technological tools, insufficient training by teachers in the digital interactive process and insufficiencies in the structuring and systematization of the digital interactive process that improves the formative contents and the development of technological tools. The study presented an applied methodology, of pre-experimental design; the sample, formed by 12 teachers and 72 students, was given the instruments that determined the analysis of the current state of the digital interactive process for the development of technological tools. After applying the strategy, the two dimensions (Didactic and Technological) were significantly transformed. In conclusion, the Digital Interactive process and its dynamics were characterized taking into account several studies where it is perceived that it implies a whole process and a series of mechanisms that must be developed in an integral way to improve the use of technological tools in the learning sessions.